Aligning a performance-based observation rubric to support a teacher performance assessment - Brown, Carmen Sherry (Journal of Interdisciplinary Studies in Education, 2017)
Preparing teacher candidates to become effective and reflective practitioners, the student teaching experience must be designed to guide candidates in applying the knowledge, theories and concepts acquired during their course of study. This analysis reviewed the components of a student teaching practicum rubric used in a teacher preparation program to determine if the performance-based assessment supported the expectations and requirements of a teacher performance assessment. The results indicated that the observation rubric used by field supervisors to rate teacher candidates aligned with the cycle of teaching effectiveness identified in the teacher performance assessment. The analysis from this study suggest that early childhood teacher preparation programs should continuously examine how faculty and course instructors are utilizing performance-based assessment and evaluation instruments in their courses, fieldwork and student teaching experiences to support the professional preparation of teacher candidates.